2022
DOI: 10.21037/atm-22-1019
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of colorectal cancer risk factors, screening, and associated factors in advanced colorectal cancer patients: a multicenter cross-sectional study in China

Abstract: Background: Colorectal cancer (CRC) is the 3rd most common malignancy globally, and its disease burden is increasing rapidly in China. But CRC patients' knowledge and awareness of CRC have not yet been examined, which could facilitate the identification of targeted population from public for intervention. Methods: A nationwide multicenter cross-sectional survey was conducted in 19 tertiary hospitals (10 cancer hospitals and 9 general hospitals) from March 2020 to March 2021 in China. During study period, all S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the study of Oh et al (2021), 71% of the participants heard about FOBT, and 84% heard about colonoscopy [36]. On the other hand, Xu et al (2022) found that 84.9% of the patients with CRC did not have information about screenings and CRC before being diagnosed [37]. In addition, the sources of information of those who had knowledge in the same study were mostly family and friends who had diagnosed with cancer, social media, and television, followed by community education [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Oh et al (2021), 71% of the participants heard about FOBT, and 84% heard about colonoscopy [36]. On the other hand, Xu et al (2022) found that 84.9% of the patients with CRC did not have information about screenings and CRC before being diagnosed [37]. In addition, the sources of information of those who had knowledge in the same study were mostly family and friends who had diagnosed with cancer, social media, and television, followed by community education [37].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Xu et al (2022) found that 84.9% of the patients with CRC did not have information about screenings and CRC before being diagnosed [37]. In addition, the sources of information of those who had knowledge in the same study were mostly family and friends who had diagnosed with cancer, social media, and television, followed by community education [37]. A high level of knowledge and awareness about scans are important factors that drive individuals to have a screening [31,38].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, ensuring training on CRC among HCWs improves patient awareness of the screening and in turn may raise demand for screening (Campioni-Norman, 2021;Katsidzira, 2019;Tfaily, 2019). Other studies have reported the importance of recommending the benefits of CRC screening to patients to improve uptake (Al Mutawah, 2018;Soylar, 2019;Carcaise-Edinboro, 2008;Alshammari, 2020), while some also recommend using reminder systems, personalized reminders, doctor validation, using relatives or friends with a history of cancer, television, and community education to increase uptake of CRC screening (Hatamian, 2021;Healthy People, 2019;Kaminski, 2020;Xu, 2022). Focused community awareness programs and CRC prevention and screening policy development are recommended by other studies in developing countries such as Iran and Ethiopia (Alshammari, 2020;Hamza, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is a nationwide multicenter cross-sectional study and the details of the study design have been published ( 18 ). In brief, a multi-stage sampling method was used to identify the 19 tertiary hospitals (10 tertiary cancer hospitals and 9 tertiary general hospitals) in China from March 2020 to March 2021.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described ( 18 ), it was estimated that more than 4445 advanced CRC patients would be enrolled. The total sample size was proportionally allocated to each region according to its population size and based on the estimated sample size, patients should be recruited from each region.…”
Section: Methodsmentioning
confidence: 99%